Immunological risk factors in recurrent pregnancy loss: guidelines versus current state of the art - Vomstein, Kilian; Feil, Katharina; Strobel, Laura; Aulitzky, Anna; Hofer-Tollinger, Susanne; Kuon, Ruben-Jeremias; Toth, Bettina (Journal of Clinical Medicine, 2021)
Around 1-5% of all couples experience recurrent pregnancy loss (RPL). Established risk factors include anatomical, genetic, endocrine, and hemostatic alterations. With around 50% of idiopathic cases, immunological risk factors are getting into the scientific focus, however international guidelines hardly take them into account. Within this review, the current state of immunological risk factors in RPL in international guidelines of the European Society of Reproduction and Embryology (ESHRE), American Society of Reproductive Medicine (ASRM), German/Austrian/Swiss Society of Obstetrics and Gynecology (DGGG/OEGGG/SGGG) and the Royal College of Obstetricians and Gynecologists (RCOG) are evaluated. Special attention was drawn to recommendations in the guidelines regarding diagnostic factors such as autoantibodies, natural killer cells, regulatory T cells, dendritic cells, plasma cells, and human leukocyte antigen system (HLA)-sharing as well as treatment options such as corticosteroids, intralipids, intravenous immunoglobulins, aspirin and heparin in RPL. Finally, the current state of the art focusing on both diagnostic and therapeutic options was summarized.
Gesehen am 28.07.2021